Bullying in school: where the danger is? A reflection based on the Attachment Theory on the dynamics abuser/abused - Gabriela Casellato (O Mundo da Saúde)
Although it is an old problem in our society, bullying has been the theme of constant investigation of researchers in the fields of health care and education wanting to understand its nature, discussing and evaluating successful interventions in different settings, especially in schools. This paper aims to reflect on the psychodynamic characteristics of bullying, based on key concepts of Attachment Theory, developed by British psychiatrist John Bowlby between the 50’s and 90’s. Our specific interest was to establish a correlation between the concepts of attachment patterns, internal operating models and strategies of social interaction abuser / abused that characterize the phenomenon of bullying. The paper was developed on the basis of the theoretical review of the main concepts of this theory, which allowed us to develop analyzes and considerations relevant to the understanding of bullying as a situation arising from social commitments related to styles of attachment: ambivalent insecure, evocative insecure, and disorganized insecure. The intention was also providing, by means of such considerations, support for new practices in different areas, from family to school, aimed at new possibilities for prevention and resolution of problems aroused.